2007
DOI: 10.1093/humrep/dem148
|View full text |Cite
|
Sign up to set email alerts
|

Examination of reproductive aging milestones among women who carry the FMR1premutation

Abstract: Possible molecular mechanisms to explain the non-linear repeat size risk for ovarian insufficiency are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
211
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(235 citation statements)
references
References 44 publications
18
211
3
2
Order By: Relevance
“…The interesting fact about this finding is that it has also been reported for ovarian insufficiency [21][22][23][24].…”
Section: Neuropsychiatric and Muscular Involvementsupporting
confidence: 63%
See 2 more Smart Citations
“…The interesting fact about this finding is that it has also been reported for ovarian insufficiency [21][22][23][24].…”
Section: Neuropsychiatric and Muscular Involvementsupporting
confidence: 63%
“…Besides Allen et al (2007) [24], other investigators have also reported a continuum of impaired ovarian function. Welt et al (2004) [25] recruited 11 women with the premutation and compared them with age-matched controls in order to show differences in menstrual cycles and hormonal changes.…”
Section: Reproductive Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…When there is a full mutation, the gene is silenced by methylation, resulting in the absence of FMR protein (FMRP) expression, which causes mental retardation. Premutations of FMR1 gene, especially those with ~8099 repeats, are the most common discovered genetic cause of spontaneous 46, XX POI, and the resultant POI is named the fragile X-related primary ovarian insufficiency (FXPOI) [6,17,22,32]. Premutation alleles remain unmethylated, and lead to increased FMR1 transcription and decreased levels of FMRP [22].…”
Section: Poi Genes On X Chromosomementioning
confidence: 99%
“…A X-linked mutation leading to an increased risk for POF is the fragile X premutation [48]. It is characterized by a large CGG repeat track (55-199 repeats) in the 5' untranslated region of the fragile X mental retardation 1 (FMR1) gene located at Xq27.3.…”
Section: Candidate Genes On the X Chromosomementioning
confidence: 99%